Tear function in patients with diabetes mellitus: A systematic review and meta-analysis - Kuo, Yu-Kai; Shao, Shih-Chieh; Lin, Erh-Tsan; Pan, Li-Yen; Yeung, Ling; Sun, Chi-Chin (Frontiers in Endocrinology, 2022)
Purpose: To examine tear function in patients with diabetes mellitus (DM). Design: Systematic review and meta-analysis. Method: We searched Embase and PubMed from database inception to March 16, 2022. We included observational studies that compared tear function between patients with and without DM. Tear function was measured using invasive tear breakup time (ITBUT) and Schirmer’s 1 test. Pooled results are presented as standard mean difference (SMD) with 95% confidence interval (CI), based on random-effects models. Results: We included 59 studies (7,234 eyes) comparing the tear function between patients with and without DM. This meta-analysis indicated that patients with DM had worse tear function than those without DM (ITBUT: SMD -0.98, 95% CI -1.27 to -0.69; Schirmer’s 1 test: SMD -0.45, 95% CI -0.64 to -0.26), and the results remained consistent in patients with different types of DM (e.g., type 1 DM and type 2 DM) and from different ethnic backgrounds (e.g., Asian vs. non-Asian). Patients with DM with poor glycemic control had worse tear function than those of the non-DM group (ITBUT: SMD -1.26, 95% CI -1.86–-0.66; Schirmer’s 1 test: SMD -0.25, 95% CI -0.48 to -0.02), while there were no significant differences in tear function between patients with DM with optimal glycemic control and non-DM groups. Conclusions: We found that patients with type 1 or type 2 DM had significantly reduced tear function. The level of tear function could be determined by glycemic control, and therefore our findings suggest that glycemic control in patients with DM is critical for maintaining tear function.